2009 Proceedings of the 55th IEEE Holm Conference on Electrical Contacts 2009
DOI: 10.1109/holm.2009.5284425
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Electrical Characteristics of the Electromagnetic Relay under Vibration and Shock Environment

Abstract: The electromagnetic relay, which has mechanical structure and break/make contacts, is affected by vibration and shock environment greatly. Contact wear and failure will be result from serious mechanical conditions. The samples used in this study were relays consisting two spring sets connected with armature component. Simulation results for a variety of vibration levels, frequencies, and shock levels are presented. Thereafter main factors and threshold conditions which influencing contact reliability were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Indeed, the value identified for the contact stiffness is coherent with the one estimated using Hertz's contact theory (Fig. 9) and the Young's modulus of the magnetic keeper is comparable to the ones usually met for this kind of relays [15,16]. The sensitivity of the first two natural frequencies in relation to the contact stiffness and Young's modulus is shown in Figs.…”
Section: Identification Of the Mechanical Parameterssupporting
confidence: 61%
See 4 more Smart Citations
“…Indeed, the value identified for the contact stiffness is coherent with the one estimated using Hertz's contact theory (Fig. 9) and the Young's modulus of the magnetic keeper is comparable to the ones usually met for this kind of relays [15,16]. The sensitivity of the first two natural frequencies in relation to the contact stiffness and Young's modulus is shown in Figs.…”
Section: Identification Of the Mechanical Parameterssupporting
confidence: 61%
“…However, Ren et al [15,16] have shown that the contact stiffness can be estimated using Hertz's contact theory (Fig. 8).…”
Section: Identification Of the Mechanical Parametersmentioning
confidence: 98%
See 3 more Smart Citations